Sari Varietas Daun Ubi Jalar Berpotensi sebagai Minuman Fungsional Antihipertensi - Ika Puspa Windardi; Eny Palupi; Ahmad Sulaeman (PT Bukuloka Literasi Bangsa, 2026)
This study aims to analyze the potential of sweet potato leaf extracts from several varieties as an antihypertensive functional beverage. The study used an experimental method with a completely randomized design to evaluate the effect of sweet potato leaf varieties (Sukuh, AC, Ungu, and Cilembu) on the organoleptic characteristics and nutritional analysis of sweet potato leaf extracts. The analyses included an organoleptic test (acceptance test using a 1–9 scale) and chemical analyses (proximate composition, potassium content, and DPPH antioxidant activity). Data were analyzed using one-way ANOVA. Panelists preferred Cilembu sweet potato leaf extract to the other varieties, but there were no differences in preference for color, aroma, taste, and viscosity. The highest potassium content was found in Sukuh sweet potato leaf extract (72.27 mg/200 mL), while Ungu sweet potato leaf extract had the highest antioxidant activity (840.92 mg/100 g AEAC). The nutritional contributions of the beverage per serving (200 mL) to energy, protein, fat, carbohydrate, and potassium requirements were 3.66%, 2.09%, 1.18%, 5.63%, and 1.22%, respectively, of the RDA for adult women aged 19–29 years. The results indicate that sweet potato leaf extract has potential as an antihypertensive functional beverage. Keywords: antihypertensive, functional beverage, sweet potato leaves